Vpliv biodizla na zgorevanje in emisijske značilke dizelskih motorjev - Hribernik, Aleš (Strojniški vestnik, 2007)
The results of investigations of the influence of biodiesel fuel and its blends with D2 fuel on the operation of diesel engines are often contradictory. Although there is a common belief that the use of biodiesel reduces soot and increases NOx emissions, the findings for CO and HC emissions tend to vary from case to case. Furthermore, there are even some reports of NOx reduction when using biodiesel. These inconsistent conclusions are caused by the non-uniformity of engine testing. These tests were performed on different engines using different combustion-chamber geometries, different fuel-injection systems, etc. In order to identify and analyze some of the possible reasons we tested two different diesel engines. The operation and emission characteristics of both engines with biodiesel and D2 fuel were measured and compared, and in-cylinder pressure traces were acquired and used for the combustion analyses. The results obtained for both engines showed that findings regarding the influence of biodiesel fuel on the combustion process and emission formation could not be generalised, and had to be interpreted as being specific to the particular engine.
Keywords: biodizel; zgorevanje; dizelski motorji